The food hygiene practices among workers in restaurants of Wasit Governorate, Iraq - Dhakam Mohammed Abbas; Sameeha Naser Abed; Rusul Abdulhameed Kadhim (Journal of the Pakistan Medical Association, 2023)
Objectives: To determine the knowledge, attitude and practices related to food hygiene among those working in restaurants. Method: The descriptive, cross-sectional study was conducted from January 5 to April 30, 2019, within restaurants located in Hay, Kut, Numania, Badra, Azizia and Suwera cities in the Wasit Governorate of Iraq. Those included using simple random sampling technique were food handlers of either gender. Data was collected using a predesigned questionnaire. Results: Of the 330 subjects from 55 restaurants, 320(96.9%) were males and 10(3%) females. The overall mean age was 31.6±9.5 years (range: 15-55 years). Overall, 193(58.4%) subjects were married, 279(84.5%) had work experience <10 years, 90(27.2%) had professional training, 212(64.2%) had studied up to secondary level, and 113(34.2%) were working as waiters. Of the total, 127(38.48%) subjects correctly described food hygiene, and 197(59.69%) acknowledged the necessity of obligatory periodical check-ups. Hygiene practice scores were poor in 223(67.57%) cases. Conclusion: The food hygiene knowledge, attitude and practice of food handlers in restaurants of Wasit governorate were found to be poor. Keywords: Restaurants, Health, Knowledge, Attitudes, Practice, Hygiene, Surveys.